Paste Thickener Design and Operation Selected to Achieve Downstream Requirements - Slottee, JS; Johnson, J (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
Successful paste or thickened tailings disposal must integrate the production, transport and disposal plan. The benefits of designing the full system in reverse flow order have been well documented. The selection of the thickener design and operation in light of the stacking and the transport rheological requirements allows for an optimum system. This paper discusses the thickener design options and how the selection of each is based on the downstream requirements.